Poverty of Dialogue or Dialogue with the Poor - Niilus, Leopoldo J. (The ecumenical review, 1967)
The major test case for Christian collaboration centres around the rich and poor nations dichotomy. (THOMAS F. STRANSKY, Church and Society, Geneva 1966, The Ecumenist, Vol. 4, No. 6, Sept.–Oct. 1966.) When the young man heard this he went away sorrowful; for he had great possessions. (Matthew 19. 22.)